2007
DOI: 10.1111/j.1551-2916.2006.01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a Sr, K, Nb (SKN) Combination to PZT(53/47) for High Strain Applications

Abstract: A lead zirconate titanate composition incorporating the dopants Sr, K, and Nb (SKN) in the specific ratio 4:1:3 has been studied.In principle, the SKN should act as a donor dopant but since its addition reduced the grain size from 11.4 lm (for 1% SKN) to 1.5 lm (for 5% SKN), the overall effect was found to be more complicated. It was observed that the addition of SKN reduced the Curie temperature, by 161C/mol (%) and broadened the dielectric peak. X-ray measurements further suggested that the ceramic was a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 16 publications
4
64
0
Order By: Relevance
“…PZT possesses superior dielectric and piezoelectric properties arising from the existence of a morphotropic phase boundary (MPB) between tetragonal and rhombohedral phases at ∼48 mol% PbTiO 3 content [5][6][7]. Piezoelectric coefficients (d 33 ) as high as 779 pC N −1 have been reported for modified PZT [8] with Curie temperatures (T C ) in the range 300-400…”
Section: Introductionmentioning
confidence: 99%
“…PZT possesses superior dielectric and piezoelectric properties arising from the existence of a morphotropic phase boundary (MPB) between tetragonal and rhombohedral phases at ∼48 mol% PbTiO 3 content [5][6][7]. Piezoelectric coefficients (d 33 ) as high as 779 pC N −1 have been reported for modified PZT [8] with Curie temperatures (T C ) in the range 300-400…”
Section: Introductionmentioning
confidence: 99%
“…The generation of oxygen vacancies reached equilibrium with the oxygen in the atmosphere, as shown in Equation (7). As a consequence of the high volatilization, the PZT was often sintered with excess PbO or lead sources (PZ) to compensate for the loss of volatile PbO [23,29,30]. Figure 2 shows the ionic conductivity change over time; the gentle slope in the N 2 zone means that the Pb-losing rate is low.…”
Section: Volatility Of Pbmentioning
confidence: 99%
“…There were published works on co-firing a Cu electrode [37] with PZTbased materials. Takayama et al [38] reported the work on fabricating Cu co-fired PZT-SKN (PZTSr(K0.25Nb0.75)O3) [20,21,23] multilayer actuators. An acrylic binder system was used to lower the burnout temperature, instead of the more widely used PVB; however, this acrylic binder was difficult to handle.…”
Section: Base Metal Co-firingmentioning
confidence: 99%
“…Some piezoelectric materials are added separately or together to the PZT system to form ternary or quaternary solid solutions, such as PZT-SKN [5], PZT-PMN [6], and PZT-PMN-PZN [7]. The Pb(Zr 0.53 ,Ti 0.47 ) O 3 -Sr(K 0.25 ,Nb 0.75 )O 3 (PZT-SKN) system were first reported by Helke et al [8].…”
Section: Introductionmentioning
confidence: 99%